Improving human resource management of the enterprise - Wu, Xueying (Харківський національний автомобільно-дорожній університет, 2024)
The relevance of the problem is due to the expediency of applying such approaches that will increase the involvement of employees in management, will allow to optimally organize labor processes; increase labor productivity. The paper analyzes the approaches to defining the concept of «human resource management»; proposes a model of «lean» human resource management; develops a balanced scorecard for assessing the effectiveness of human resource management; develops a methodology for analyzing the effectiveness of human resource management; develops an optimization model for resource allocation to improve employee performance; develops a methodology for assessing the impact of labor organization on the effectiveness of human resource management.
Keywords: management; human resources; system; lean production; balanced scorecard; mechanism